Winning at war seven keys to military victory throughout history - Potholm, Christian P. (Rowman & Littlefield, 2010)
In Winning at War, Christian Potholm explains how seven variables technology, sustained ruthlessness, discipline, receptivity to innovation, protection of military capital from civilians and rulers, will, and the belief that there will always be another war have served as predictors of military success over time and across cultures. He provides case studies of their implementation, from ancient battles to today. What are the independent variables that determine success in war? Drawing on 40 years of studying and teaching war, political scientist Christian P. Potholm presents a 'template of Mars, ' seven variables that have served as predictors of military success over time and across cultures. In Winning at War, Potholm explains these variables technology, sustained ruthlessness, discipline, receptivity to innovation, protection of military capital from civilians and rulers, will, and the belief that there will always be another war and provides case studies of their implementation, from ancient battles to today